Penerapan Asas Itikad Baik dalam Penyelesaian Sengketa Perdata - Alysia Hapsari, Leilani; Setiyawan, Anang (Zaaken: Journal of Civil and Business Law, 2023)
This article discusses the application of the principle of good faith in the settlement of civil disputes. It emphasizes the distinction between law and justice, highlighting the necessity of positive law to regulate legal relationships and prevent self-help remedies. The principle of good faith is crucial in the formation of agreements to prevent conflicts and disputes. Civil disputes, involving conflicting parties, are to be resolved through accountability and responsibility, which are integral components of agreements. The principle of good faith is also fundamental in international law and plays a significant role in shaping and executing the obligations of parties in cooperation agreements. Mediation is identified as a crucial aspect of dispute resolution, both outside and within the judicial process, with the aim of achieving amicable settlements. The mediation process consists of three stages: pre-mediation, mediation implementation, and final implementation. The article underscores the importance of good faith in all stages of dispute resolution, whether in preparation, negotiation, or agreement execution, and emphasizes the significance of parties' commitment and presence in mediation as indicators of good faith. Keywords: Good Faith, Civil Dispute Resolution, Treaty Law, Contract Law, Mediation, Litigation, Non-Litigation, Settlement, Court-Connected Mediation   Abstrak Artikel ini membahas penerapan asas itikad baik dalam penyelesaian sengketa perdata. Artikel ini menekankan perbedaan antara hukum dan keadilan, menyoroti perlunya hukum positif untuk mengatur hubungan hukum dan mencegah upaya penyelesaian sendiri. Asas itikad baik sangat penting dalam pembentukan perjanjian untuk mencegah konflik dan sengketa. Sengketa perdata, yang melibatkan pihak-pihak yang saling bertentangan, harus diselesaikan melalui akuntabilitas dan tanggung jawab, yang merupakan komponen integral dari perjanjian. Asas itikad baik juga merupakan hal yang fundamental dalam hukum internasional dan memainkan peran penting dalam membentuk dan melaksanakan kewajiban para pihak dalam perjanjian kerja sama. Mediasi diidentifikasi sebagai aspek penting dalam penyelesaian sengketa, baik di luar maupun di dalam proses peradilan, dengan tujuan untuk mencapai penyelesaian secara damai. Proses mediasi terdiri dari tiga tahap: pra-mediasi, pelaksanaan mediasi, dan pelaksanaan akhir. Artikel ini menggarisbawahi pentingnya itikad baik dalam semua tahap penyelesaian sengketa, baik dalam persiapan, negosiasi, maupun pelaksanaan kesepakatan, dan menekankan pentingnya komitmen dan kehadiran para pihak didalam mediasi sebagai indikator itikad baik. Kata Kunci: Itikad Baik, Penyelesaian Sengketa Perdata, Hukum Perjanjian, Hukum Kontrak, Mediasi, Litigasi, Non-Litigasi, Perdamaian, Court-Connected Mediation